Gender Differences in Idiopathic Pulmonary Fibrosis: Are Men and Women Equal? - Sesé, Lucile; Nunes, Hilario; Cottin, Vincent; Israel-Biet, Dominique; Crestani, Bruno; Guillot-Dudoret, Stephanie; Cadranel, Jacques; Wallaert, Benoit; Tazi, Abdellatif; Maître, Bernard; Prévot, Gregoire; Marchand-Adam, Sylvain; et al. (Frontiers in Medicine, 2021)
Background: Idiopathic pulmonary fibrosis (IPF) is characterized by a male predominance. The aim of the study was to explore gender differences in a well-designed French multicentre prospective IPF cohort (COhorte FIbrose, COFI) with a 5-year follow-up. Methods: Between 2007 and 2010, 236 patients with incident IPF were included in COFI. Gender characteristics were compared using a t-test, Chi-squared test and ANOVA, as appropriate. Survival analyses were performed. Results: Fifty-one (22%) females and 185 (78%) males with an average age at diagnosis of 70.1 ± 9.20 and 67.4 ± 10.9 years, respectively, were included in the cohort. Women were significantly less exposed to tobacco smoke [never n = 32 (62.7%) vs. n = 39 (21.1%), p < 0.001] and to occupational exposure [n = 7 (13.7%) vs. n = 63 (34.1%), p = 0.012]. Baseline forced vital capacity, % of predicted (FVC%) was significantly better in women compare to men (83.0% ± 25.0 v. 75.4% ± 18.7 p = 0.046). At presentation honeycombing and emphysema on CT scan were less common in women [n = 40 (78.4%) vs. n = 167 (90.3%) p = 0.041] and [n = 6 (11.8%) vs. n = 48 (25.9%) p = 0.029], respectively. During follow-up fewer women were transplanted compared to men [n = 1 (1.96%) vs. n = 20 (10.8%) p = 0.039]. Medians of survival were comparable by gender [31 months (CI 95%: 28–40) vs. 40 months (CI 95%: 33–72) p = 0.2]. After adjusting for age and FVC at inclusion, being a woman was not associated to a better survival. Conclusions: Women appear to have less advanced disease at diagnosis, maybe due to less exposure history compare to men. Disease progression and overall survival remains comparable regardless gender, but women have less access to lung transplantation.